Determinants and Consequences of Auditor Deviant Behavior - Suwardi Suwardi; Khomsiyah Khomsiyah (Eduvest - Journal of Universal Studies, 2024)
Audit quality became an important issue after a global corporate scandal that revealed auditors' inability to detect financial statement fraud, leading to corporate bankruptcies and scandals. Auditors' deviant behavior, such as inindependence and incompetence in the implementation of duties, has the potential to damage audit quality. This study aims to analyze the factors that cause auditor behavior to deviate and their impact on audit quality in Jakarta, Indonesia. The factors analyzed include time budget pressure, task complexity, client importance, and organizational commitment. This survey involved 103 respondents who were selected by purposive sampling. The results showed that time budget pressure, client importance, and organizational commitment contributed to auditor deviant behavior, while task complexity had no significant effect. The auditor's deviant behavior has a negative impact on the quality of audits, which in turn can damage public trust in the audit profession. This study provides insights for regulators and public accounting firms to identify factors that affect auditor behavior and audit quality degradation, and develop approaches to minimize deviant behavior without sacrificing audit value for external users.